2023
DOI: 10.1177/20595131221141083
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of clinical psychology input into burns multidisciplinary follow-up clinics

Abstract: Introduction Research highlights the complex psychological needs that patients and their families can face following a burn injury, regardless of the objective severity of the injury and often beyond the timeframe of physical healing. Identification of psychological needs at different stages post-burn recovery is therefore a key role of clinical psychologists working in burn care services. Method This paper presents audit data collected across a two-year period in routine paediatric and adult multidisciplinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Therefore, there may be value in implementing follow-up psychosocial screenings at multiple stages of a burn patients' treatment [11,31]. One study found that the presence of psychologists at outpatient appointments enabled the identification and treatment of burn-related psychological concerns that were not met earlier in the treatment pathway [32]. Consistently, most participants in this study suggested that increasing psychological presence following discharge and during outpatient appointments would facilitate access.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, there may be value in implementing follow-up psychosocial screenings at multiple stages of a burn patients' treatment [11,31]. One study found that the presence of psychologists at outpatient appointments enabled the identification and treatment of burn-related psychological concerns that were not met earlier in the treatment pathway [32]. Consistently, most participants in this study suggested that increasing psychological presence following discharge and during outpatient appointments would facilitate access.…”
Section: Discussionsupporting
confidence: 59%
“…Psychosocial screening in the adult burns patient population is recommended to allow psychological care to be preventative by identifying those with arising psychosocial difficulties and to help normalise psychological reactions after a burns injury [10]. Screening has been found to be feasible to implement and can identify distress amongst patients from the early stages of hospitalisation [10] to outpatient settings [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…NBCS recommend that appropriate treatment should be given based on psychosocial needs identified through screening [1]. Three levels of psychological care have been identified: (1) basic screening and gauging psychological need; (2) psychological assessment, psychoeducation and low-level intervention such as emotional care; (3) psychological therapy and signposting to other appropriate services [10,12]. Utilising a tiered approach to assessing and supporting psychological needs throughout the pathway can embed clinical psychology within burns multidisciplinary teams (MDT) and highlight its value [12].…”
Section: Introductionmentioning
confidence: 99%